Functions Ofeducationalactivitiesin Cultural Centersfrom Thecommunity Development Perspective - Urboniene, Aiste; Jurėnienė, Virginija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
This paper aims to analyse the role that cultural centres in Lithuania and Lithuanian cultural organisations in the Kaliningrad region and Belarus play in organizing educational activities for the local communities. The aim of this article is to identify functions ofthe educationalactivitiesof cultural centres and Lithuanian cultural organisations revealing theirimpact on thelocal communitydevelopment. Semi-structured interviews were conducted in 4 Lithuanian cultural centres and 6 Lithuanian cultural organisations of border regions in Lithuania, Belarus, and Russia, the Kaliningrad region. The sample consists of 55 informants from Lithuanian cultural communities and cultural centres. The content analysis and comparative analysis methods were applied for the data analysis. The study revealed that educational activities would lead to active participation of members in community development. The following functions of educational activitieswere identified: dissemination of knowledge, empowerment, self-realization, enlightenment, value development, recreation, communication, national identitystrengthening, and community mobilization.